2016
DOI: 10.7243/2052-6180-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of entomopathogenic fungi in atlantic forest soils

Abstract: Knowledge of the composition and distribution of native entomopathogenic fungal species are essential to evaluate the potential of biological control in a given ecosystem. In this study, 10 soil samples were collected in two seasons (dry and rainy) in the Curió Municipal Natural Park in Paracambi and the presence of entomopathogenic fungi species was evaluated. The isolation was carried out using two methods: the bait method with Galleria mellonella and Tenebrio molitor larvae and the selective media Agar Pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
(62 reference statements)
0
11
0
1
Order By: Relevance
“…The dominance of B. bassiana in soils collected from various types of forests is also confirmed by studies conducted in Denmark [37], Finland [7], Poland [27,35,38,39], Japan [40], Italy [41,42] Spain [43,44], Austria [45], Mexico [46], Brasil [47] and Portugal [48]. Niemczyk et al [21], examining the occurrence of Beauveria spp.…”
Section: Discussionmentioning
confidence: 75%
“…The dominance of B. bassiana in soils collected from various types of forests is also confirmed by studies conducted in Denmark [37], Finland [7], Poland [27,35,38,39], Japan [40], Italy [41,42] Spain [43,44], Austria [45], Mexico [46], Brasil [47] and Portugal [48]. Niemczyk et al [21], examining the occurrence of Beauveria spp.…”
Section: Discussionmentioning
confidence: 75%
“…The maintenance of this virulence above the levels of the enzyme production may also be related to the genetic diversity of these fungi, which may be influenced by the habitat in which each isolate was obtained (Mora et al 2016). A research comparing the location and isolation method showed that fungi isolated from soil resulted to a high mortality rate of H. armigera caterpillars (Kalvnadi et al 2018).…”
Section: Conidial Viabilitymentioning
confidence: 99%
“…Very little information exists on the isolation of entomopathogenic fungi for the control of insect pests in Nigeria, but the use of entomopathogenic Fungi for the control of Mosquito has long been recognized from different part of the world [25,15,6,9]. Moreover, this fungus specie isolated from soil had been previously detected in the soil from different part of the world along with some of the most widely used groups of fungal pathogens such as Beauveria bassiana [26][27]. The results of this study indicate that, Entomopathogenic fungi; M. anisopliae was pathogenic to 4th instars larvae of C. quinquefasciatus and percentage mortality reaches 90%.…”
Section: Resultsmentioning
confidence: 99%